2016
DOI: 10.1016/j.jmbbm.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A mechanical argument for the differential performance of coronary artery grafts

Abstract: Coronary artery bypass grafting (CABG) acutely disturbs the homeostatic state of the transplanted vessel making retention of graft patency dependent on chronic remodeling processes. The time course and extent to which remodeling restores vessel homeostasis will depend, in part, on the nature and magnitude of the mechanical disturbances induced upon transplantation. In this investigation, biaxial mechanical testing and histology were performed on the porcine left anterior descending artery (LAD) and analogs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…However, it has been shown that the cornea is largely governed by the structure of the stroma which consists primarily of a lamellae of type-I collagen fibrils embedded in a hydrated proteoglacan matrix. Gradual recruitment of the embedded (load bearing) wavy collagen fibrils with increasing IOP give rise to a nonlinear mechanical behavior of the cornea with a stiffening effect at IOP greater than 60 mmHg [30, 41]. Yet, the range of pressure prescribed in this study covers normal range of IOP and it showed that cornea behaved linearly within a range of IOPs between 2 and 4 kPa [42].…”
Section: Disuccsionmentioning
confidence: 99%
“…However, it has been shown that the cornea is largely governed by the structure of the stroma which consists primarily of a lamellae of type-I collagen fibrils embedded in a hydrated proteoglacan matrix. Gradual recruitment of the embedded (load bearing) wavy collagen fibrils with increasing IOP give rise to a nonlinear mechanical behavior of the cornea with a stiffening effect at IOP greater than 60 mmHg [30, 41]. Yet, the range of pressure prescribed in this study covers normal range of IOP and it showed that cornea behaved linearly within a range of IOPs between 2 and 4 kPa [42].…”
Section: Disuccsionmentioning
confidence: 99%
“…There is evidence that graft longevity is dependent on the target vessel and its capacity to provide a good runoff flow. Advocates of the good runoff theory suggest that sequential anastomoses achieve a better runoff and lesser peripheral resistance to flow and therefore, improved long‐term patency 41,45‐48 . While some evidence supports this statement a recent paper found worse rates of LSV graft failure with sequential anastomoses 41,45‐48 …”
Section: Resultsmentioning
confidence: 99%
“…Advocates of the good runoff theory suggest that sequential anastomoses achieve a better runoff and lesser peripheral resistance to flow and therefore, improved long‐term patency 41,45‐48 . While some evidence supports this statement a recent paper found worse rates of LSV graft failure with sequential anastomoses 41,45‐48 Flow measurement: Transit time flow measurement (TTFM) may provide the surgeon with a tool for assessing both anastomosis quality and distal runoff while still in the operating theater; the current guidelines are that it should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…where sr c is the estimation of wave speed from the regression analysis. The surface wave speed can be related to the elastic modulus of tissue as [34] For soft tissue under low frequency harmonic excitation, Voigt's model, which consists of a spring of elasticity µ 1 and a damper of viscosity µ 2 connected in parallel, has been proven to be effective in modeling the linear viscoelastic materials [35][36][37][38]. The wave dispersion curve of wave speed c s with respect to the excitation frequency ω can be formulated by, 2 2 2 1 2…”
Section: Methods Lung Ultrasound Surface Wave Elastography (Luswe) Tecmentioning
confidence: 99%